Evaluation of Bridge Condition Values Using the Bridge Management System (BMS) Method (Case Study: Three Bridge Units in Majalengka Regency) - Muhammad Wafi Hariry; Amanatullah Savitri (Fakultas Teknik Sipil dan Perencanaan, 2024)
The bridge is an infrastructure whose existence is an important part of the transportation system and economic movement of a region. If the bridge is damaged or collapses, it will affect the transportation and development of the distribution of people and goods. Thus, maintenance of the bridge is a must. The Bridge Management System (BMS) method is a standard mechanism for evaluating the condition and function of bridges. The BMS can also be used to decide on the maintenance needed to maintain a bridge under certain circumstances. The assessment was carried out in the form of a visual assessment of the bridge to evaluate the general condition of the bridge. This research was conducted at three bridges in Majalengka Regency, namely the Citeureup Bridge, the Cideres Bridge, and the Talang Bridge. Evaluation is carried out by conducting inventory surveys and detailed inspections of objects (bridge damage elements). Then each element is given a point weight of 1 and 0 according to its damage level from the lowest (level 5) to the highest (level 1), which means the bridge completely collapsed. Elements or groups of elements are given a weight from 0 to 5 where 5 represents the total score of 5 categories. The categories are Structure (S), Damage Level (R), Damage Volume (K), Element Function (F), and Damage Effect (P). Condition studies, technical screening, and evaluation of handling for the Citeureup Bridge, Cideres Bridge, and Talang Bridge each resulted in the following conditions: 3 (Heavy Damage – Rehabilitation), 2 (Slightly Damaged – Routine Maintenance), and 2 (Slightly Damaged – Maintenance) Routine).